(untitled) (Pedagogy of Higher and Secondary Education, 2016)
Yashchuk T. A. Educational services market and labor market: problem of interaction. Interaction mechanism of clients and users on educational services market is observe in the article. Tools of economic management mechanism of quality educational services and training structure in the field of knowledge and needs of enterprises are examined. The imbalance between demand and supply of specialists in the market is shown. The discrepancy between labour market demand for specialists with higher education and their training volume is a global problem of modern economic and political system of our country. The introduction of new educational technologies, immersion in approaches of the European education by the national high school is an oriented point for youth, but not on filling of the real highly paid vacant areas of modern labour market. The most important indicator of competitive specialist is the development and improvent of labour quality, and high qualification of workers, who master the latest technology, and are able to work with modern equipment. The necessity for cooperation between the education market and labour is shown in the article. To eliminate the negative interaction it is necessary to provide the interaction between the labour market and the education market by studying their condition and the development of short-term forecasts of employment opportunities. To solve this problem it is necessary to activate participation of higher education institutions in addressing the problem of overcoming the imbalance of education market and the labour market, providing the economy of the country with highly skilled labour force. An international experience shows that marketing services of higher education institutions that study the needs of the labour market, requirements of employers must become an integral part of the management structure of higher education institution.